A medical device for spinal motion restriction : Development of a device for safe and efficient patient handling - Jersenius, Ylva; Möller, Erika (Luleå tekniska universitet, Institutionen för ekonomi, teknik och samhälle, 2020)
Prehospital emergency care is facing a paradigm shift. Spinal motion restriction (SMR) is a way to treat trauma patients with symptoms of spinal injury. It was earlier entitled as ‘routine SMR’, and included spine board and cervical collar. During the 2000s, it has been noted that there is a lack of scientific evidence that proves the benefits with ‘routine SMR’. This led an expert group to the development of the national guidelines, that were published in 2019. The national guidelines can be described as ‘selective SMR’, where the cervical collar and spine board is excluded. It means that the SMR shall be adapted to the patient and not the equipment. Furthermore, the patient should be involved as much as possible in the treatment. This master thesis has been conducted at the Luleå University of Technology (LTU), in collaboration with AB Germa. The objective was to enable paramedics (the users in this project) to provide trauma patients with safe and efficient SMR by improving the usability of available or future products for SMR. Therefore, the project aim was to deliver a conceptual suggestion with feedback from the users. Furthermore, a mapping with experienced problems was delivered, and a review of the available medical devices with recommendations on how the future product development of medical devices for SMR could head in a user-centred direction. The theoretical framework included both ergonomics, including anthropometry and anatomy, and semiotics to involve both the physical and cognitive aspects of good usability, as a complement to the contextual immersion to be able to develop a thought through conceptual suggestion. The contextual immersion involved contact with Sweden’s 21 regions, and 16 paramedics. Through visits, interviews, and observations information was gathered about available medical devices for SMR, and challenges that paramedics are facing with them where mapped. This was compiled in a user need specification, which formed the basis for the idea generation. The ideation resulted in ...